PENGARUH ACCELERATED LEARNING CYCLE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2015)
Mathematical problem solving ability is an ability that is included in Indonesia national education goals, but its achievement is still relatively low. This quasi-experimental research examines the ability of solving mathematical problems through the application of Accelerated Learning Cycle. The subjects were seventh grade students in Riau Province, which were divided into an experimental group and a control group. The research instrument used was mathematical problem solving ability test, and the data were analyzed using Mann-Whitney test and two ways ANOVA. The results of this study indicate that there was a significant effect of Accelerated Learning Cycle on the overall students’ mathematical problem-solving skills (p = 0.000, p
Keywords: accelerated learning cycle; kemampuan pemecahan masalah matematis; mathematical problem solving ability